Improved compliance and patient satisfaction with estradiol vaginal tablets in postmenopausal women previously treated with another local estrogen therapy - Minkin MJ; Maamari R; Reiter S (Dove Medical Press, 2013)
Mary Jane Minkin,1 Ricardo Maamari,2 Suzanne Reiter31Obstetrics, Gynecology, and Menopause, Temple Medical Center, New Haven, CT, 2Hormone Therapy, Novo Nordisk Inc, Princeton, NJ, 3Mid-County Health Center, Largo, FL, USAAbstract: Up to half of all postmenopausal women will experience changes in the genitourinary tract induced by the hypoestrogenic state, collectively known as vaginal atrophy. Vaginally administered local estrogen therapy (LET) is the standard of care for symptoms of vaginal atrophy that do not respond to nonhormonal interventions. Several LET formulations are available, and choice of therapy is based largely on patient needs and preferences. This online survey of postmenopausal LET users was conducted to investigate reasons for switching to vaginal estradiol tablets from other formulations and to evaluate factors associated with patient preference for and compliance with use of LET. Data was analyzed from 73 respondents currently using estradiol vaginal tablets who have previously used the estradiol vaginal ring, estradiol vaginal cream, and/or conjugated estrogen vaginal cream. Patients in this survey rated vaginal symptoms of vaginal atrophy as being more bothersome than urinary symptoms. Respondents preferred their current treatment with the vaginal tablet to their previous treatment with a cream or ring. The preference for tablets over creams was mainly related to formulation and application rather than to any perceived safety issues. Tablets were perceived as efficacious, convenient, and neat to apply. The study participants also reported a longer duration of tablet use compared with creams or rings, and greater compliance with vaginal tablets than with vaginal cream. This study provides new insights into reasons for patient noncompliance with estrogen cream or ring therapy that can be used to maximize patient adherence with LET.Keywords: vaginal atrophy, local estrogen therapy, estradiol, vaginal ring, vaginal tablet, vaginal cream, conjugated estrogen vaginal cream